Kebaruan gaya ungkap dalam cerpen-cerpen berlatar budaya Bali - I Gusti Ayu Agung Mas Triadnyani (Pusat Kajian Bali Universitas Udayana, 2017)
There are many recurring social conflicts in Bali that originate in customs and cultures such as caste conflict, exclusion (kasepekang), and issues surrounding black magic. These conflicts are often used as inspiration for Balinese writers to write literary works such as novels and short stories. From the setting story on Balinese social conflict, it can be seen how public perception of the conflict and also how the author’s style expresses social conflict through the art of literature. This article aims to find out the various social and cultural issues that inspire literary writers to write works of literature and how they deliver it so as to create works that educate and entertain. Two sets of short stories entitled Padi Dumadi (The Incarnation of Rice, 2007) by Adnyana Ole and Mandi Api (Bathed by Fire, 2008) by Aryantha Soethama, two of Bali’s leading authors. The approach used in this study is structural approach that examines the elements of the text. Analysis shows that there is a tendency of Balinese authors to raise cultural issues with a new style of expression using the element of surprise at the ending of the story.